Sustainable Islamic Education Management: Integrating Islamic Values and the Sustainable Development Goals (SDGs) - Lilis Supriatin; M. Saroni; Nuruddin Araniri (PT. Anagata Sembagi Education, 2025)
This article explores the integration of Islamic values with the Sustainable Development Goals (SDGs) within the framework of sustainable Islamic education management. Islamic education plays a strategic role in advancing sustainable development, as it embodies universal principles such as justice, trustworthiness (amanah), responsibility, and compassion (rahmah) that are aligned with the vision of the SDGs. This study employs a qualitative approach through a systematic literature review and conceptual analysis to formulate a theoretical framework for sustainable Islamic education management. The findings indicate a strong alignment between the objectives of Islamic law (maqāṣid al-sharī‘ah) and the principles of sustainability, particularly in relation to quality education, gender equality, social justice, and environmental preservation. This integration can be achieved through the development of curricula that are responsive to global issues, the implementation of transformative spiritual leadership, inclusive institutional governance, and learning evaluations that emphasize social, moral, and ecological dimensions. The article proposes a conceptual model, the Islamic Sustainable Education Management Framework, which bridges Islamic spirituality with the SDGs. It contributes to the literature on Islamic education management from a sustainability perspective while offering practical recommendations for policymakers and managers of Islamic educational institutions.